Disturbance Observer-Based Robust Control and Its Applications: 35th Anniversary Overview - Sariyildiz, Emre; Oboe, Roberto; Ohnishi, Kouhei (IEEE transactions on industrial electronics (1982), 2020)
Disturbance observer (DOB) has been one of the most widely used robust control tools since it was proposed by Ohnishi in 1983. This paper introduces the origins of DOB and presents a survey of the major results on DOB-based robust control in the last 35 years. Furthermore, it explains DOB's analysis and synthesis techniques for linear and nonlinear systems by using a unified framework. In final section, this paper presents concluding remarks on DOB-based robust control and its engineering applications.